Korelasi Pola Asuh Orang Tua Dan Status Pekerjaan Terhadap Kedisiplinan Anak Di RA Nurul Yaqin Kecamatan Medan Timur - Anita Anita (AL-HANIF: Jurnal Pendidikan Anak dan Parenting, 2022)
A person's development, especially the formation of attitudes, habits and behavior patterns in childhood can be said to be entirely in the form of parenting. One of the developments that can be seen in a child is the development of discipline. This study aims to determine the relationship between parenting and work on child discipline at RA Nurul Yaqin, East Medan District. The sample in this study consisted of 33 parents who had children aged 4-7 years. This type of research is non-parametric correlation with a cross-sectional approach. The data analysis technique used univariate and bivariate tests with Chi Square Fisher's Exact Test. The results showed that most of the parenting patterns were non-democratic as many as 24 people (72.7%), the most parents' work was not working as many as 21 people (63.6%), and good child discipline as many as 21 people ( 63.6%). There is a significant relationship between parenting and child discipline in RA Nurul Yaqin, Medan Timur District (p value 0.012) and there is no significant relationship between parental work and child discipline in RA Nurul Yaqin, Medan Timur District (p value 1,000).